Optimal Load Frequency Controller of Two Area Interconnected Power System Using Physical Constraints - Sunil Kumar, ahid, MD Mokaddam, Dr. Rashmi Agarwal (International Journal of Advanced Science and Technology, 2020)
This paper is shows the performance of the load frequency controller used in the two area power system model. These three controllers are conventional PI controller, Genetic Algorithm proportional plus integral controller (GA PI Controller) and Bacteria Foraging Optimization Algorithm proportional plus integral controller (BFOA PI Controller). To optimum the load in the power system with the help of governor turbine, thermodynamics process, filters and communication channel, three physical constraints are used i.e. Dead band, Time delay and Generation rate constant (GRC). Consider a two area no-reheat thermal power system to equipped with proportional plus integral controller (PI), BFOA PI and GA PI controller to reduce the system oscillation, damping ratio and settling time. The performance of PI based GA controller and BFOA controller is improved the efficiency of the power system. Simulation results show the better performance of BFOA PI controller as compared to the optimized GA PI controller and conventional PI controller over wide range of operating conditions and system parameter variations. The main object of this paper is getting the stable response after introducing physical constraint with conventional controller.